2017
DOI: 10.1111/cns.12717
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of DEC1 contributes to the neurotoxicity induced by MPP+ by suppressing PI3K/Akt/GSK3β pathway

Abstract: Downregulation of DEC1 contributes to MPP -induced neurotoxicity by suppressing PI3K/Akt/GSK3β pathway.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
19
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 61 publications
3
19
0
Order By: Relevance
“…It has been revealed that DEC1 overexpression and knockdown inversely regulate the expression levels of β-catenin and phosphatidylinositol-4,5-bisphosphate 3-kinase catalytic subunit α in glucocorticoid-induced osteoporotic changes in SaoS-2 cells and mice ( 17 ). Furthermore, downregulation of DEC1 contributes to 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine-induced neurotoxicity by suppressing the PI3K/Akt/glycogen synthase kinase 3 β (GSK-3β) pathway ( 18 ). The Wnt/β-catenin signaling pathway is one of the most important signal transduction pathways in cells, and serves an essential role in regulating normal cell proliferation, movement, differentiation and tumorigenesis ( 19 , 20 ).…”
Section: Introductionmentioning
confidence: 99%
“…It has been revealed that DEC1 overexpression and knockdown inversely regulate the expression levels of β-catenin and phosphatidylinositol-4,5-bisphosphate 3-kinase catalytic subunit α in glucocorticoid-induced osteoporotic changes in SaoS-2 cells and mice ( 17 ). Furthermore, downregulation of DEC1 contributes to 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine-induced neurotoxicity by suppressing the PI3K/Akt/glycogen synthase kinase 3 β (GSK-3β) pathway ( 18 ). The Wnt/β-catenin signaling pathway is one of the most important signal transduction pathways in cells, and serves an essential role in regulating normal cell proliferation, movement, differentiation and tumorigenesis ( 19 , 20 ).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have reported that DEC1 can be induced in a cell type-specific manner by various extracellular stimuli, such as hypoxia, growth factors, hormones and cytokines (35)(36)(37)(38). DEC1 can also act as a transcriptional factor through interactions with the PI3K/Akt/glycogen synthase kinase 3β signaling pathway to promote osteogenic activity and to relieve 1-methyl-4-phenylpyridinium-induced cytotoxicity (39,40). A recent study showed that activation of the Akt/P53/P21 signaling pathway promotes proliferation and migration of human osteosarcoma cells, and activation of the Akt/P53/P21 signaling pathway induced the downregulation of DEC1 (21); however, the direct effect of DEC1 on regulating the Akt/P53/P21 signaling pathway remains unknown.…”
Section: Discussionmentioning
confidence: 99%
“…MiR-30a-5p regulated GLT-1 through the PKCα pathway in the SNpc of MPTP-treated mice Since we found that GLT-1 expression and function was indeed regulated by miR-30a-5p but that Slc1a2 was not a target gene of miR-30a-5p, we hypothesized that miR-30a-5p regulates GLT-1 via an undetermined pathway. As potential intermediaries between miR-30a-5p and GLT-1, we chose several signaling molecules that have been associated with PD, namely PI3K, PKCα, STAT3, and mTOR [50][51][52][53][54]. As expected from their known roles in PD, western blots of the active, phosphorylated (p-) form of these proteins showed that PI3K (p < 0.01) (Fig.…”
Section: Mir-30a-5p Regulated the Expression And Function Of Glt-1 In Vitromentioning
confidence: 99%